2018
DOI: 10.1016/j.biopha.2018.08.145
|View full text |Cite
|
Sign up to set email alerts
|

Bergapten inhibits liver carcinogenesis by modulating LXR/PI3K/Akt and IDOL/LDLR pathways

Abstract: Oxysterol receptors LXRs (α and β) are recently reported to be one of the novel and potential therapeutic targets in reducing cell proliferation and tumor growth in different system model. Activation of LXRs is correlated with modification of PI3K/Akt pathway. LXRs are also found to play a critical role in maintaining lipid homeostatais by regulating ABCA1, IDOL, SREBP1, LDLR and also certain lipogenic genes such as FASN and SCD1. In the present study a potential furanocoumarin, Bergapten (BeG) has been evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…In apoptosis, cytosol Bax releases caspase-activating Cyt-c. The caspase-8 (extrinsic apoptosis) or -9 (intrinsic apoptosis), is activated which further activates caspase-3, essential to propagates apoptotic signal [49][50][51][52][53]. Cell shrinkage and chromatin condensation helps in apoptosis [54].…”
Section: Pi3k/akt Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In apoptosis, cytosol Bax releases caspase-activating Cyt-c. The caspase-8 (extrinsic apoptosis) or -9 (intrinsic apoptosis), is activated which further activates caspase-3, essential to propagates apoptotic signal [49][50][51][52][53]. Cell shrinkage and chromatin condensation helps in apoptosis [54].…”
Section: Pi3k/akt Inhibitionmentioning
confidence: 99%
“…Highly expressed SREBPs play important roles in malignancies, connecting oncogenic signaling to lipid metabolism alterations, leading to rapid tumor growth. PI3K-Akt pathway is inhibited by LXRs [53,75]. Bergapten inhibits liver carcinogenesis (HepG2) by activating LXRs, inhibiting PI3K/Akt that reduced SREBP-1, fatty acid synthase (FASN), stearoyl-CoA desaturase-1 (SCD1), thereby preventing fatty acid synthesis and tumor growth [53].…”
Section: Pi3k/akt Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several published studies, compounds 1-3 have shown potent anticancer activity in numerous cancer cell lines but these have not included lung cancer. [28][29][30][31][32][33] For example, psoralen (1) inhibited proliferation by modulating the Wnt/β-catenin pathway in breast cancer cells. 28 Xanthotoxin (2) has been reported to possess antitumor activity in breast cancer cells 29 and inhibits the activation of AP-1 and NF-κB subunits.…”
mentioning
confidence: 99%
“…Numerous animal studies showed that overexpression of IDOL gene in mouse liver caused the development of hypercholesterolemia and atherosclerosis 8 . Instantaneous adenoviral overexpression of mouse IDOL gene in wildtype model resulted in a significant decrease in LDLR protein and an increase in LDL-C levels 9,10 . Other possible downstream of IDOL includes VLDLR and ApoER2 11 .…”
mentioning
confidence: 99%